The crystal structure of poly[((2-(4,5-dihydro-1H-pyrazol-4-yl)-1,3-dioxoisoindoline-5-carbonyl)oxy)(1-(dimethylamino)ethoxy)zinc[II]], C16H14ZnN4O5 - Mo Zong-Wen; Liu Jie-Wei; Liang Gang; Liu Guo-Zhu (Zeitschrift für Kristallographie - New Crystal Structures, 2024)
C16H14ZnN4O5, orthorhombic, Pbcn (no. 60), a = 19.0280(5) Å, b = 9.0707(2) Å, c = 20.0081(6) Å, V = 3453.34(16) Å3, Z = 8, Rgt (F) = 0.0396, wRref (F 2) = 0.0953, T = 230(2) K.